THE EFFECT OF SOCIAL FAMILY SUPPORT ON PSYCHOLOGICAL ADJUSTMENT ON ASSIMILATION INTERESTED RESIDENTS IN ASSIMILATION OF INTERESTED CITIZENS IN CLASS II BAPAS PATI - Maki Zaenudin Subarkah; Elsafira Maghfiroti Resyanta (Polteknik Ilmu Pemasyarakatan, 2021)
In the early of 2020, Indonesia was shocked with a new virus, namely SARS-CoV-2 or COVID-19. Many policies has taken by the government to preventing the spread of COVID-19. In overcrowded prison, there is limited space to have a safe distance. The option to reduce the spreading is creating acceleration of assimilation at home After serving their prison terms in prisons and detention centers and having their families returned due to the COVID-19 pandemic, they are certainly facing various psychological problems and problems in their daily life. To be able to survive with these conditions, humans must make psychological adjustments In the process of adapting to the environment, family social support is needed. The aims of this study to determine the relationship between family social support and psychological adjustment to asimilation clients at Class II Probation Board of Pati. This study uses a quantitative approach. The process of taking research samples is done by simple random technique, 93 study samples were obtained. Data collection was carried out with the distribution of questionnaires and literature study. Management of data was carried out using the SPSS 25 program. The data collection used the family social support scale and the psychological adjustment scale Data analysis used simple regression analysis with a determination coefficient =0,676 and a correlation coefficient=0,822 (p<0.05) with an effective contribution of 67,6%. This study found a strong positive relation between family social support and psychological adjusment in Probation Client.